Factors Associated with Serious Injuries among Adolescents in Ghana: Findings from 2012 Global School Health Survey - Martin Ackah; Mohammed Gazali Salifu; Hosea Boakye (The Scientific World Journal)
Introduction. Injuries are of public health concern and the leading cause of residual disability and death among teenagers, especially in low- and middle-income countries (LMICs). In Ghana, the burden of injury among adolescents is under-reported. Hence, the study sought to determine the prevalence of serious injuries (SI) and the potential factors influencing these injuries among school children in Ghana. Methods. This study was conducted in Ghana among Junior High School (JHS) and senior high school students (SHS) using the 2012 Global School-Based Student Health Survey (GSHS) data. The GSHS employed two-stage cluster sampling method. Serious injuries (SI) and independent factors were measured via self-administered questionnaires. Pearson chi-square test between each explanatory variable and serious injuries was conducted and the level of statistical significance was set at 5%. The significant variables from the chi-square test were selected for multiple logistic regression analysis. Multiple logistic regression was performed to estimate the adjusted odds ratio (AOR) at 95% confidence interval (CI). Results. The prevalence of SI in the past 12 months was 66% [CI=61.8–70.2] . The most common cause of SI was fall, 36%. The common types of injuries were cut/stab wounds and broken/dislocated bone. In the multiple logistic regression analysis, after controlling for other variables, educational level (AOR = 0.64, CI = 0.44–0.90, p < 0.015), suicidal ideation (AOR = 1.58, CI = 1.00–2.48, p < 0.002), suicidal attempt (AOR = 1.88, CI = 1.29–2.72, p < 0.001), having at least one close friend (AOR = 1.49, CI = 1.17–1.89, p < 0.002), school truancy (AOR = 1.66, CI = 1.31–2.09, p < 0.000), smoking marijuana (AOR = 2.64, CI = 1.22–5.69), and amphetamine use (AOR = 2.95, CI = 1.46–5.69) were independently associated with SI. Conclusion. The findings of the study established a high prevalence of SI among adolescents in Ghana, with cut/stab wound and broken/dislocated bone being the most reported type of injuries. This study also revealed that factors such as educational level, suicidal ideation, suicidal attempt, at least one close friend, school truancy, smoking marijuana, and amphetamine use are associated with SI among the adolescents. Therefore, pragmatic interventional programs should be targeted at these factors to curb the rate of SI among junior and senior school students.